Jeckey Ng Kah Poo receives Presidential Award of Academic Excellence from Board of Engineers Malaysia BEM - Hafizatulazlin, Abdul Aziz (UMPSA, 2024)
GAMBANG, 21 October 2023 - The COVID-19 pandemic did not prevent Jeckey Ng Kah Poo, a graduand of Bachelor of Electrical Engineering (Electronics) with Honours, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) from being more focused and not giving up.